Targeted Deletion of Centrin in Leishmania braziliensis Using CRISPR-Cas9-Based Editing - Sharma, Rohit; Avendaño Rangel, Francys; Reis-Cunha, João Luís; Marques, Larissa Pinheiro; Figueira, Claudio P.; Borba, Pedro B.; Viana, Sayonara M.; Beneke, Tom; Bartholomeu, Daniella C.; de Oliveira, Camila I. (Frontiers in Cellular and Infection Microbiology, 2022)
Leishmania braziliensis is the main causative agent of Tegumentary Leishmaniasis in the Americas. However, difficulties related to genome manipulation, experimental infection, and parasite growth have so far limited studies with this species. CRISPR-Cas9-based technology has made genome editing more accessible, and here we have successfully employed the LeishGEdit approach to attenuate L. braziliensis. We generated a transgenic cell line expressing Cas9 and T7 RNA polymerase, which was employed for the targeted deletion of centrin, a calcium-binding cytoskeletal protein involved in the centrosome duplication in eukaryotes. Centrin-deficient Leishmania exhibit growth arrest at the amastigote stage. Whole-genome sequencing of centrin-deficient L. braziliensis (LbCen−/−) did not indicate the presence of off-target mutations. In vitro, the growth rates of LbCen−/− and wild-type promastigotes were similar, but axenic and intracellular LbCen−/− amastigotes showed a multinucleated phenotype with impaired survival following macrophage infection. Upon inoculation into BALB/c mice, LbCen−/− were detected at an early time point but failed to induce lesion formation, contrary to control animals, infected with wild-type L. braziliensis. A significantly lower parasite burden was also observed in mice inoculated with LbCen−/−, differently from control mice. Given that centrin-deficient Leishmania sp. have become candidates for vaccine development, we propose that LbCen−/− can be further explored for the purposes of immunoprophylaxis against American Tegumentary Leishmaniasis.